2018
DOI: 10.6063/motricidade.13476
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, fatigue and quality of life during a clinical adjuvant treatment of breast cancer: a comparative study

Abstract: It was our objective to compare the physical activity, fatigue and quality of life of patients during breast cancer treatment and to investigate the association between these variables. Participated in this study 122 women in clinical treatment at the Cancer Research Center (CEPON) in Florianópolis, SC. We used a questionnaire with general information, physical activity (IPAQ - short), fatigue (Piper fatigue) and quality of life (EORTC QLQ - C30). One-way ANOVA with Scheffe's post-hoc, Chi-square, and univaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
1
4
0
3
Order By: Relevance
“…The authors concluded that physical activity is an essential behavior to enhance wellbeing in cancer patients. 12 Regardless of the type of treatment or age, increased levels of daily physical activity were associated with improvements in quality of life and fatigue. 14 Patients satisfaction with their functionality levels and increased muscle strength and cardiorespiratory resistance were some mechanisms mentioned by the authors, directly interfering in the perceived exhaustion and consequently in quality of life.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The authors concluded that physical activity is an essential behavior to enhance wellbeing in cancer patients. 12 Regardless of the type of treatment or age, increased levels of daily physical activity were associated with improvements in quality of life and fatigue. 14 Patients satisfaction with their functionality levels and increased muscle strength and cardiorespiratory resistance were some mechanisms mentioned by the authors, directly interfering in the perceived exhaustion and consequently in quality of life.…”
Section: Discussionmentioning
confidence: 96%
“…14 Patients satisfaction with their functionality levels and increased muscle strength and cardiorespiratory resistance were some mechanisms mentioned by the authors, directly interfering in the perceived exhaustion and consequently in quality of life. 12,29 A limitation of our study was its cross-sectional design, as it does not allow us to establish temporality relationships among the investigated variables. Another limitation was the inclusion of different types of cancer, because there is not enough evidence on whether physical activity is a protective factor for all types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…En lo que se refiere a la imagen que las mujeres tienen de sí mismas, se observa un cambio positivo tras la intervención psicológica en la condición experimental, así como una disminución de la afección emocional que manifestaban en las evaluaciones preliminares. Tal y como señalan Boing et al (2018), los cambios físicos consecuentes de la enfermedad generan una gran perturbación emocional en las pacientes puesto que la apariencia física tras la cirugía y el tratamiento entra en conflicto con el propio concepto que tienen sobre la mujer, lo que también disminuye la percepción de su propia calidad de vida (Teo et al, 2016). El presente estudio también muestra que las mujeres recuperan la funcionalidad en dossier Mejora de la funcionalidad física y emocional tras un programa de intervención multicomponente en mujeres con cáncer de mama…”
Section: Discussionunclassified
“…En concreto, el diagnóstico del cáncer de mama ha aumentado un 12% durante el 2018 en países como España o México, lo que lleva a considerar el cáncer de mama como un problema de salud pública relevante (Sociedad Española de Oncología Médica, 2019). Precisamente es en personas afectadas de cáncer de mama donde se han realizado mayores estudios a través de evaluaciones psicológicas que han valorado el impacto que tiene la enfermedad en la calidad de vida percibida relacionada con la imagen corporal y el tratamiento médico recibido (Boing et al, 2018;Teo et al, 2016). Este constructo requiere una gran relevancia al dotarse de un significado subjetivo y personal y que repercute en la salud física, psicológica y social.…”
Section: Introductionunclassified
“…Επίσης, υπάρχουν δύο κύριοι παράγοντες που εκθέτουν τους ασθενείς με καρκίνο μαστού σε υψηλότερο κίνδυνο αϋπνίας: (α) υψηλότερο ποσοστό αγγειοκινητικής συμπτωματολογίας και (β) συνυπάρχουσες καταστάσεις όπως η κόπωση, η κατάθλιψη και η ανησυχία (Boing, de Bem Fretta, Vieira, Denig, Bergmann, & de Azevedo Guimarães, 2018;Savard, Davidson, Ivers, Quesnel, Rioux, Dupéré... & & Morin, 2004).…”
Section: καρκίνος και ποιότητα ζωήςunclassified